Organizational Transformation from the Directorate of Goods and Services Procurement to the Directorate of Supply Chain Management - Ide Ambardi, Muhamad; Suliantoro, Hery; Budiawan, Wiwik (Pelopor Publikasi Akademika, 2025)
In the modern business environment, organizational transformation has become an essential strategy for enhancing efficiency, adaptability, and competitiveness. As companies face rapid technological and market changes, restructuring internal systems and redefining operational paradigms are necessary to maintain strategic alignment. This study examines the organizational transformation from the Directorate of Goods and Services Procurement to the Directorate of Supply Chain Management (PBJ to SCM) as a paradigm shift from an administrative to a strategic function within a corporate context. Using a descriptive qualitative method and a case study approach, the research explores how this transformation was implemented through organizational restructuring, role redefinition, competency development, and the integration of digital supply chain systems. The findings reveal that these initiatives not only improved procurement efficiency but also enhanced cross-divisional collaboration, transparency, and strategic decision-making. Moreover, the transformation contributed to greater responsiveness to Industry 4.0 demands, positioning the company to compete effectively in a dynamic market environment. This study provides practical insights for organizations undertaking similar organizational transformations, emphasizing that successful change management requires strong leadership commitment, continuous capability development, and digital integration as key enablers for sustainable organizational performance.